Integrasi Numerasi pada Pelajaran Non-Matematika - Awi Dassa; Said Fachry Assagaf; Syahrullah Asyari (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Numeracy is currently the focus of elementary and middle school education in Indonesia. Strengthening numeracy should not only rely on mathematics classroom. Contributions from other lessons can also be usefull to strengthen students' numeracy skills. This article reports an investigation into 23 non-mathematics junior high school teachers in Takalar Regency, South Sulawesi in designing the integration of numeracy learning in their lessons. There are four lessons found in this activity, namely Indonesian Language, Natural Sciences, Social Sciences, and Arts and Culture lessons. It is expected that the results of this report can strengthen numeracy activities in various subjects at the junior high school level.